2015
DOI: 10.1016/j.biopsycho.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The late positive potential: A neural marker of the regulation of emotion-based approach-avoidance actions?

Abstract: The ability to regulate our emotional responses is crucial to effective functioning in daily life. Whilst there has been extensive study of the brain potentials related to valenced stimuli, the neural basis of the ability to regulate actions elicited by these remains to be clarified. To address this, 40 volunteers undertook an approachavoidance paradigm. In the congruent condition, participants approached pleasant and avoided unpleasant stimuli. In the incongruent condition, the opposite was the case, requirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 46 publications
7
27
0
Order By: Relevance
“…This latter condition instructs individuals to apply response modulation. Previous studies in the typical population have shown that reaction times are faster in the congruent compared to the incongruent condition as one would predict (Bamford et al, 2015;Bamford & Ward, 2008;Chen & Bargh, 1999;Phaf, Mohr, Rotteveel, & Wicherts, 2014). This congruency effect reflects the additional effort/cognitive resources needed to override the natural approachavoidance action tendencies; a greater congruency effect therefore indexes more difficulties in response modulation.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…This latter condition instructs individuals to apply response modulation. Previous studies in the typical population have shown that reaction times are faster in the congruent compared to the incongruent condition as one would predict (Bamford et al, 2015;Bamford & Ward, 2008;Chen & Bargh, 1999;Phaf, Mohr, Rotteveel, & Wicherts, 2014). This congruency effect reflects the additional effort/cognitive resources needed to override the natural approachavoidance action tendencies; a greater congruency effect therefore indexes more difficulties in response modulation.…”
Section: Introductionmentioning
confidence: 95%
“…The approach-avoidance task in the current study was based on the computer-based task used by Bamford et al (2015) and Bamford and Ward (2008). A valenced picture (7 by 5 cm in size; either positive or negative) was presented on each trial on a white background.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations